The Study of the English Article System Errors Made by High School Students in the United Arab Emirates. - DERBAS, MOHAMED NOUR (2021)
Abstract The purpose of this study is to determine the errors made by grade 12 students in the use of definite and indefinite articles in one of the secondary schools for boys located in Sharjah educational zone. English articles system can be confusing for Arab ESL/EFL students, because the Arabic language only has a definite article and no indefinite article. In contrast, the English language contains both. The study sought to identify the most often occurring errors and to offer teaching and learning strategies to solve these obstacles. Moreover, it is discovered that the most frequently occurring errors made by the study's sample are intralingual errors caused by ineffective and old approach in teaching the article system. As a result, several pedagogical applications were recommended to assist English teachers in teaching students how to acquire the English article system. It is hoped and advised that the findings of this study would be used to develop exercises to assist students in developing a more appropriate use of the definite and indefinite articles. Keywords: English article system, error, sources of errors